Reaching point break: understanding the lived experience of being overwhelmed - Dael, Nele; Meister, Alyson; Krings, Franciska (Frontiers in Organizational Psychology, 2025)
Modern workplaces subject employees to relentless pressures and demands, marked by perpetual change, uncertainty, and intricate challenges. Accordingly, many employees are struggling to cope, leaving them feeling “overwhelmed”. Despite its colloquial prevalence, the experience of being overwhelmed remains a powerful yet ill-defined phenomenon. This inductive study draws on 94 first-person narratives and ratings to examine the affective components, context and workplace impact of this debilitating experience. From our thematic analysis emerges the definition of overwhelm as a distinct affective state occurring at the perceived tipping point when situational demands are appraised as exceeding available resources, and is marked by heightened alertness yet bodily fatigue, limited outward expression, withdrawal or mental freeze, and the conscious experience of predominantly negative feelings. Recurring appraisals of demands were unpredictable, unreasonable, and outweighing an individual's resources, common to stress-related affective states with an almost exclusively negative valence. We highlight common antecedents, consequences, and coping strategies that might support employees and organizations to mitigate its detrimental outcomes. We conclude by offering directions for future research and practical interventions aimed at enhancing employee well-being.